CLSM assessment of tubule penetration and bacterial leakage evaluation of two resin-based sealer - Baldissera, Renata; Rosa, Ricardo Abreu da; Santini, Manuela Favarin; Nascimento, Angela Longo do; Kuga, Milton Carlos [UNESP]; Pereira, Jéferson Ricardo; Montagner, Francisco; Só, Marcus Vinícius Reis (My University, 2014)
Aim: The aims of this study were to assess the penetration of two endodontic sealers (salicylate and epoxy resin-based sealers) into dentinal tubules using CLSM; and to evaluate the bacterial leakage of roots filled with the same sealers associated with gutta-percha. Material and Methods: For sealer penetrability assessment, thirty bovine roots were instrumented and divided into three groups: AHP: EDTA + filling with AH Plus and gutta-percha (n=10), MTAF: EDTA + filling with MTA Fillapex and gutta-percha (n=10), control group: canals were not irrigated with EDTA and were filled with gutta-percha and AH Plus (n=5) or MTA Fillapex (n=5). Rhodamine B was added to the sealers in order to provide adequate fluorescence. The roots were transversely sectioned 3mm from the apex to enable CLSM analysis. Leakage was evaluated for turbidity of the broth in a split chamber model system for 30 days, using Enterococcus faecalis as a microbial marker. Thirty roots were instrumented and divided in four grupos: AHP: filling with AH Plus and gutta-percha (n=10); MTAF: filling with MTA Fillapex and gutta-percha (n=10); positive control: filling with gutta-percha without sealer (n = 5); negative control: sealing with cyanoacrylate to test the seal of the system (n = 5). Results: The medians for dentinal tubule penetration were 6.8% (AHP) and 6.6% (MTAF) (P = 0.82). The average time for bacterial leakage was 8 days in both experimental groups (P = 0.79). Conclusion: MTA Fillapex and AH Plus presented similar behavior regarding dentinal tubule penetration and bacterial leakage.
Keywords: Endodontics; Dental leakage; Bacterial; Confocal microscopy; Root canal filling materials